Journals based on applications: An attempt to improve students' learning about composite materials - Lundström, T. Staffan; Booth, Shirley A. (European journal of engineering education, 2002)
In a course on composite materials for fourth-year students at Chalmers University of Technology, students are required to write journals as a complement to the more traditional teaching approach. The journals comprise a series of reports relating the theory currently being treated to an application object, and are sent to the teacher by e-mail for comments. These give the students the opportunity to make use of the theoretical knowledge they meet in each section of the course by reflecting on how it is applicable to a real application. The goal is for better, more integrated understanding, in that, on the one hand, the students should understand the importance of each part of the course and, on the other hand, they should be able to relate the parts to one another, and to practical application. In this paper, we describe the goals and strategies of the change to teaching, we analyse the ways that students approach the journal writing task and we discuss ways in which the journals can improve the quality of student learning.